Exploring the transcriptomic landscape of moyamoya disease and systemic lupus erythematosus: insights into crosstalk genes and immune relationships - Guo, Qingbao; Fan, Yan-Na; Xie, Manli; Wang, Qian-Nan; Li, Jingjie; Liu, Simeng; Wang, Xiaopeng; Yu, Dan; Zou, Zhengxing; Gao, Gan; Zhang, Qian; Hao, Fangbin; et al. (Frontiers in Immunology, 2024)
Background: Systemic Lupus Erythematosus (SLE) is acknowledged for its significant influence on systemic health. This study sought to explore potential crosstalk genes, pathways, and immune cells in the relationship between SLE and moyamoya disease (MMD).We obtained data on SLE and MMD from the Gene Expression Omnibus (GEO) database. Differential expression analysis and weighted gene co-expression network analysis (WGCNA) were conducted to identify common genes. Subsequently, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed on these shared genes. Hub genes were further selected through the least absolute shrinkage and selection operator (LASSO) regression, and a receiver operating characteristic (ROC) curve was generated based on the results of this selection. Finally, single-sample Gene Set Enrichment Analysis (ssGSEA) was utilized to assess the infiltration levels of 28 immune cells in the expression profile and their association with the identified hub genes.Results: By intersecting the important module genes from WGCNA with the DEGs, the study highlighted CAMP,